2020
DOI: 10.1186/s12964-020-00565-2
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and TCFs/LEF signaling discordantly regulate IL-6 expression in astrocytes

Abstract: Background: The Wnt/β-catenin signaling pathway is a prolific regulator of cell-to-cell communication and gene expression. Canonical Wnt/β-catenin signaling involves partnering of β-catenin with members of the TCF/LEF family of transcription factors (TCF1, TCF3, TCF4, LEF1) to regulate gene expression. IL-6 is a key cytokine involved in inflammation and is particularly a hallmark of inflammation in the brain. Astrocytes, specialized glial cells in the brain, secrete IL-6. How astrocytes regulate IL-6 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 101 publications
0
17
1
Order By: Relevance
“…In liver cancer stem cells, Shh/Gli-regulated cell functions were also found to be mediated by activation of the IL-6/STAT3 pathway, but whether there is a similar direct effect of Shh-blockade on IL-6-mediated STAT3 signaling was not reported [59]. Of interest is that in addition to Shh, astrocytes and microglia secrete IL-6 [60,61], and it was reported that treatment with tumors, blockade of STAT3 in our mouse model resulted in significant disruption of Smo-driven MB tumor induction. While blockade of tumor formation did not occur in all mice, it is plausible that tumor initiation in our study may have temporally preceded drug administration and/or drug penetration to the stem-like cell population was not complete in a portion of mice tested.…”
Section: Accepted Articlementioning
confidence: 99%
“…In liver cancer stem cells, Shh/Gli-regulated cell functions were also found to be mediated by activation of the IL-6/STAT3 pathway, but whether there is a similar direct effect of Shh-blockade on IL-6-mediated STAT3 signaling was not reported [59]. Of interest is that in addition to Shh, astrocytes and microglia secrete IL-6 [60,61], and it was reported that treatment with tumors, blockade of STAT3 in our mouse model resulted in significant disruption of Smo-driven MB tumor induction. While blockade of tumor formation did not occur in all mice, it is plausible that tumor initiation in our study may have temporally preceded drug administration and/or drug penetration to the stem-like cell population was not complete in a portion of mice tested.…”
Section: Accepted Articlementioning
confidence: 99%
“…TCF3 functions as a transcriptional regulator in neuronal differentiation, with an impact on many other genes ( 68 ). Interestingly, TCF3 can regulate IL-6 signaling, which is disturbed in DM1 ( 69 , 70 ). Since there are differences in splicing aberrations between brain regions in DM1, our findings may not always be representative for other brain regions than the frontal cortex ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used specific primers directed toward a specific locus within IL-6 proximal promoter, which contains adjacent CRE and NF-IL6 motifs and is located 200 bp upstream from the IL-6 translation initiation site [41,70]. Site directed mutations within CRE or NF-IL6 motifs reduced IL-6 promoter activity in luciferase assays, and eradicated CREB and C/EBPβ bindings in electrophoretic mobility shift assays [65,71], suggesting that these motifs are crucial for IL-6 transcription regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been shown that TNFα increases the DNA binding capacity of cyclic AMP Response Element-binding protein (CREB) to CRE-like element (CRE) motif [39], whereas IL-1β enhancing CCAAT/enhancer binding protein beta (C/EBPβ) binds to a consensus site named nuclear factor that specifically binds to an IL1-responsive element in the IL-6 gene (NF-IL6) [40]. Notably, adjacent CRE and NF-IL6 motives are mapped at the IL6 proximal promoter at nucleotides 204-227 upstream from the translation start site (Figure 3A) [41]. Since IL-1β and TNFα cooperatively induced IL-6 transcripts, we examined the ability of CREB and C/EBPβ to bind to the endogenous IL-6 promoter in adipocytes treated with TNFα, IL-1β, alone or in combination, using chromatin immunoprecipitation (ChIP), followed by Q-PCR.…”
Section: Il-1β/tnfα Stimulation Increases Creb Binding At Il-6 Promotermentioning
confidence: 99%